What is the impact of cost overrun risk on the final cost of building construction projects in the government - Fathoni, Ridlo Nur (The International Journal of Politics and Sociology Research, 2024)
Cost overrun occurs due to factors affecting cost components that often escape control, so there is a tendency to increase as a result of weak control by the company, either from the planning consultant or the Public Works and Spatial Planning Office (DPUPR). The purpose of this study was to determine the effect of cost overrun risk on the final cost of building construction projects in the Boyolali Regency government. The research method used is descriptive method. The survey results in the form of interviews and questionnaires from experts and respondents were processed with parametric analysis, statistical methods with descriptive analysis, correlation analysis, and regression analysis. The result of this study is to determine the cost overrun risk variables that have the most influence on the final cost performance of building construction projects in the Boyolali Regency Government, namely the problem of unavailability and foreign currency fluctuations and the acceleration of the schedule and given recommendations for action to control it.